Zaini Dahlan’s Feminism Ideology in Quranic Translation - Lail, Moh Jamalul; Sya'roni, Mokh; Muhammad, Hasyim (Sawwa: Jurnal Studi Gender, 2023)
In 1997, the Islamic University of Indonesia (UII) Yogyakarta published Qur’an Karim dan Terjemahan Artinya (QKTA). This translation significantly differs from the official version of the Ministry of Religious Affairs of the Republic of Indonesia and contemporary translations. Emerging during Indonesia's transition from the New Order to Reformation, QKTA played an important role, which motivates this study using Teun A. van Dijk's critical discourse analysis. This research investigates QKTA's position amidst the growing feminist discourse in Indonesia. This article specifically examines its impact on the verses translated: QS. al-Baqarah [2]: 228, QS. al-Nisā' [4]: 1, and 34, and QS. al-Nabā' [78]: 33. These verses were chosen because feminist interpreters often criticize them for their patriarchal perspective. These verses show QKTA's partiality to the feminist point of view. The findings of this article state that the social context and cognition of the translator influence the translation.  This can be seen from the translations that apply a lot of linguistic rhetoric, such as majāz, kināyah, and euphemism.